TAFSIR ESKATOLOGIS: Studi Manuskrip Abad ke-19 di Palembang - Putri, Maulida; Nafsi, Lathifah; Wahyuni, Syafira Mardhotilla (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2025)
This research is a philological study of a classic manuscript on the theme of Ahlussunnah wal Jama'ah creed from the collection of Kemas Haji Andi Syarifuddin. This study aims to reconstruct the original manuscript and reveal the contents of the creed teachings contained therein, especially in protecting Muslims from deviant ideologies. The methods used include heuristic stages (searching and identifying manuscripts), codicological descriptions, transliteration of texts from Arabic script to Latin script, critical editing, and content analysis with a theological approach. The results of the study show that this manuscript emphasizes the main principles of Ahlussunnah wal Jama'ah creed, such as belief in Allah and the reward for that belief, namely heaven or hell, and explains the concept in a distinctive style that is easily understood by the local community. This study emphasizes the importance of preserving the scientific heritage of Islam Nusantara, as well as the contribution of local scholars in spreading and maintaining the purity of creed through written works.